2020
DOI: 10.1007/s10592-020-01270-w
|View full text |Cite
|
Sign up to set email alerts
|

The rise of a large carnivore population in Central Europe: genetic evaluation of lynx reintroduction in the Harz Mountains

Abstract: Large carnivores have made a successful comeback across human-dominated landscapes in Central Europe. The Eurasian lynx, for instance, has been actively reintroduced in different regions. Genetic diversity is quickly eroding in these isolated, small populations, questioning the long-term success of lynx reintroductions. To track population development and genetic diversity in a reintroduced lynx population, we used microsatellite analysis and mtDNA haplotyping based on 379 samples collected during the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
1
25
0
Order By: Relevance
“…For example, the Harz Mountains population was entirely founded using captive‐bred lynx, although they were maternally reared (Anders & Sacher, 2005). This population has fared well in the last two decades and is considered stable (Mueller et al., 2020). Dispersing individuals have almost reached neighboring populations, which has even fuelled speculation of the greater propensity for exploration of captive animals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Harz Mountains population was entirely founded using captive‐bred lynx, although they were maternally reared (Anders & Sacher, 2005). This population has fared well in the last two decades and is considered stable (Mueller et al., 2020). Dispersing individuals have almost reached neighboring populations, which has even fuelled speculation of the greater propensity for exploration of captive animals.…”
Section: Discussionmentioning
confidence: 99%
“…It was initially expected the lynx would have come from the BBA population along the forested borderland between the Czech Republic and Germany, but genetic assignment suggested its origin in the Harz Mts in Germany (169 km distant). This movement shows the potential for gene flow between the BBA and the Harz population, both isolated populations with low (Bull et al 2016), or declining levels of genetic diversity (Mueller et al 2020). Admixture between different subspecies could pose a risk because it can lead to low or in an extreme case zero fitness of progeny through loss of local adaptations (Lynch 1991).…”
Section: Population Origin Of Dispersersmentioning
confidence: 99%
“…Further, in each case, the number of released animals was low and in some cases the animals were even closely related. This has inevitably resulted in low levels of genetic diversity and an increased risk of inbreeding depression (Breitenmoser-Würsten and Obexer-Ruff 2003;Sindičić et al 2013;Bull et al 2016;Mueller et al 2020). However, it has been shown that even single dispersing individuals may considerably enhance the genepool and population viability in small populations (Frankham et al 2002;Bull et al 2016;Åkesson et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, western Eurasian lynx populations were better connected and genetically more homogeneous, but in the past two centuries, anthropogenic factors disrupted the formerly existing connectivity among European populations [16,17]. Because previous molecular studies on L. lynx focused mainly on European and Northern Asian populations [15,16,[19][20][21][22][23][24][25][26][27], most information on the species' phylogeography and evolutionary history derives from these northern Palearctic populations. However, during Pleistocene glaciations, species spreading towards Europe were stopped in their migration by extended ice sheets and remained in glacier-free southern refugia where they accumulated high genetic diversity [7,28].…”
Section: Introductionmentioning
confidence: 99%